Building Leadership Skills in Educational Leadership: A Case Study of Successful School Principals - Osias Kit T. Kilag; Marsha Heyrosa-Malbas; Durivil D. Ibañez; Gliezel A. Samson; John Michael Sasan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study examined the key characteristics and practices of successful school principals, as perceived by teachers, parents, and students. Four themes emerged from the data: collaborative decision-making, relationship building, continuous professional development, and visionary leadership. Successful principals were found to prioritize collaboration, involving all members of the school community in decision-making processes, and building positive relationships with staff, students, and parents. They also placed a strong emphasis on continuous professional development, both for themselves and their staff, and were able to articulate a clear vision for their school and communicate that vision effectively to all stakeholders. The study highlights the importance of effective school leadership in promoting a positive school culture and improving student achievement. The findings suggest that successful school leaders must be able to work collaboratively, build positive relationships, prioritize ongoing professional development, and articulate a clear vision for their school. These characteristics and practices can serve as a guide for aspiring and current school leaders, as well as for those involved in the recruitment and selection of school principals